Alloying and surface composition of model Pd-Ag films synthesized by electroless deposition - Tarditi, Ana Maria (2012)
PdAg model films and real composite membranes were prepared by sequential electroless deposition on top of porous stainless steel supports. Their surface properties were investigated by X-ray photoelectron spectroscopy (XPS), Angle resolved XPS and sputtering depth profile. It was shown that the surface of the alloy was strongly enriched in silver after the annealing treatment up to 500 °C on hydrogen stream. A relationship between the Ag 3d5/2 core-level binding energy shift and the silver surface composition was observed from the XPS data obtained with the model samples. The surface composition of real membranes after both hydrogen permeation and reaction experiments showed silver enrichment, in agreement with the data obtained from the model sample.